The effect of a kind of hyperbranched polyester with different carbon length on flowability for crude oil. (15th February 2018) - Quan, Hongping; Chen, Liao; Huang, Zhiyu; Wang, Jinyu; Zheng, Cunchuan
Highlights: A kind of hyperbranched polyester with different carbon length is designed as flow improver and reduce the viscosity of crude oil significantly. The mixed carbon-chains matched with the carbon chain distribution of saturated hydrocarbon have better ability than the single on inserting into the wax crystal is demonstrated by XRD. A possible assembly model is proposed that hyperbranched structure could raise the effect to disperse agglomerates. Abstract: In this work, using the pentaerythritol with phthalic anhydride and different long-carbon chain alcohols to synthesize a kind of hyperbranched polyester (FI) as flow improver for crude oil. The evaluation test shows FI could decline the viscosity by 65% at most on 50 °C, from 33430 mPa·s to 11670 mPa·s. Through further analyzed, TGA results confirm the designed compounds was successfully synthesized. XRD demonstrates the mixed carbon chain matched with the carbon chain distribution of saturated hydrocarbon have better ability than the single on inserting into the wax crystal. IR results indicate the reaction between the carboxyl of FI and the amino hydroxyl and hydroxyl of asphaltene and resin respectively. SEM photographs show FI react to the asphaltene and resin on the macro. In the further, the assembly model presents the FI with hyperbranched structure could increase the separation effect to improve the flowability of the crude oil.